Boundedness of Multilinear Calderón-Zygmund Operators on Grand Variable Herz Spaces - Hammad Nafis; Humberto Rafeiro; Muhammad Asad Zaighum (Journal of Function Spaces)
In this paper, we prove the boundedness of multilinear Calderón-Zygmund operators on product of grand variable Herz spaces. These results generalize the boundedness of multilinear Calderón-Zygmund operators on product of variable exponent Lebesgue spaces and variable Herz spaces.